International Classification of Diseases - 11th revision: from design to implementation - Manuella Santos Carneiro Almeida; Luis Ferreira de Sousa Filho; Patrícia Moreira Rabello; Bianca Marques Santiago (Universidade de São Paulo, 2020)
ABSTRACT The World Health Organization launched in May 2019 the new International Classification of Diseases (ICD), 11th revision. As a contribution to this transition, this article aims to present the main changes of the revised version of the classification and indicate the most pressing challenges. After 30 years of the ICD-10 publication, we identified significant challenges regarding the new classification, which was presented for adoption by several countries and will be in force in January 2022. The purpose of the preview is to allow countries to plan its use and train their professionals. The new version is completely digital, thus reducing notification errors and facilitating the dissemination and consolidation of this new version. The update highlights the advances in scientific understanding, and it demands structural actions and implementation efficiency from governments, so that everyone who deals with assistance can speak the same language, on a global scale.